Penerapan Model Discovery Learning Dalam Pembelajaran Menelaah Diksi Konotatif Bertema Profil Pelajar Pancasila Pada Puisi di Kelas X SMK Bina Warga Bandung - Renalianti Dastiani; R. Panca Pertiwi Hidayati; Frilia Shantika Regina (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This study aims to describe: (1) the author's ability to carry out learning activities by applying the discovery learning model in learning to examine connotative diction themed Pancasila student profiles in poetry in class X SMK Bina Warga Bandung; (2) the ability of students in learning to examine connotative diction themed Pancasila student profiles in poetry using the discovery learning model in the experimental class; (3) the difference in student learning outcomes before and after using the discovery learning model in the experimental class and the direct learning model in the control class; (4) the difference in the effectiveness of the discovery learning model in the experimental class and the direct learning model in the control class. The approach used in this research is a quantitative approach. The method used is a pseudo-experimental method with a nonequivalent control group design. The results of this study are: (1) the author is able to carry out learning with the discovery learning model in learning to examine connotative diction themed Pancasila student profiles by obtaining a score of 3.8 and 3.72 with a very good category; (2) students are able to examine connotative diction themed Pancasila student profiles in poetry by using the discovery learning model, as evidenced by the average results that have increased during the posttest to 80.22; (3) there is a difference in learning outcomes when the pretest in the experimental class is 48.96 and increases during posttest activities to 80.22. While the average value of the pretest in the control class was 57.83 and increased during the posttest to 57.83; (4) there is a difference in the effectiveness of the discovery learning model and the direct learning model seen from the results of testing the independent sample t test Sig. (2-tailed) value is 0.000 <0.05, which means that learning using the discovery learning model is considered more effective because it has a good improvement during the posttest activity.